First operation of the JUNGFRAU detector in 16-memory cell mode at European XFEL - Marcin Sikorski; Marco Ramilli; Raphael de Wijn; Viktoria Hinger; Aldo Mozzanica; Bernd Schmitt; Huijong Han; Richard Bean; Johan Bielecki; Gábor Bortel; Thomas Dietze; Gyula Faigel; et al. (Frontiers in Physics, 2023)
The JUNGFRAU detector is a well-established hybrid pixel detector developed at the Paul Scherrer Institut (PSI) designed for free-electron laser (FEL) applications. JUNGFRAU features a charge-integrating dynamic gain switching architecture, with three different gain stages and 75 μm pixel pitch. It is widely used at the European X-ray Free-Electron Laser (EuXFEL), a facility which produces high brilliance X-ray pulses at MHz repetition rate in the form of bursts repeating at 10 Hz. In nominal configuration, the detector utilizes only a single memory cell and supports data acquisition up to 2 kHz. This constrains the operation of the detector to a 10 Hz frame rate when combined with the pulsed train structure of the EuXFEL. When configured in so-called burst mode, the JUNGFRAU detector can acquire a series of images into sixteen memory cells at a maximum rate of around 150 kHz. This acquisition scheme is better suited for the time structure of the X-rays as well as the pump laser pulses at the EuXFEL. To ensure confidence in the use of the burst mode at EuXFEL, a wide range of measurements have been performed to characterize the detector, especially to validate the detector alibration procedures. In particular, by analyzing the detector response to varying photon intensity (so called ‘intensity scan’), special attention was given to the characterization of the transitions between gain stages. The detector was operated in both dynamic gain switching and fixed gain modes. Results of these measurements indicate difficulties in the characterization of the detector dynamic gain switching response while operated in burst mode, while no major issues have been found with fixed gain operation. Based on this outcome, fixed gain operation mode with all the memory cells was used during two experiments at EuXFEL, namely in serial femtosecond protein crystallography and Kossel lines measurements. The positive outcome of these two experiments validates the good results previously obtained, and opens the possibility for a wider usage of the detector in burst operation mode, although compromises are needed on the dynamic range.